Erwinia herbicola isolates from alfalfa plants may play a role in nodulation of alfalfa by Rhizobium meliloti. - Handelsman, J (1985)
Erwinia herbicola was isolated from roots of plants derived from surface-sterilized seeds of all alfalfa varieties that were tested. Some of these E. herbicola strains affected nodulation by certain strains of Rhizobium meliloti. In previously published work we presented the isolation of slow-and fast-nodulating variants from a single culture of R. meliloti 102F51. In the absence of E. herbicola, the slow-nodulating variant induced the formation of nodules on alfalfa as rapidly as the faster-nodulating strain. The rates of nodulation by the faster-nodulating variant were the same in the presence and absence of E. herbicola. All of the previously reported slower-nodulating strains derived from R. meliloti 102F51 nodulated more rapidly on sterilized plants than in the presence of certain E. herbicola isolates.